Effect of Switching to Once-Weekly Semaglutide on Non-Alcoholic Fatty Liver Disease: The SWITCH-SEMA 1 Subanalysis - Hiroshi Nomoto; Yuka Takahashi; Yoshinari Takano; Hiroki Yokoyama; Kazuhisa Tsuchida; So Nagai; Aika Miya; Hiraku Kameda; Kyu Yong Cho; Akinobu Nakamura; Tatsuya Atsumi (MDPI AG, 2023)
Non-alcoholic fatty liver disease (NAFLD) is an important common comorbidity in individuals with type 2 diabetes (T2DM). Although some glucagon-like peptide-1 receptor agonists (GLP-1RAs) have beneficial effects on NAFLD, the efficacy of once-weekly semaglutide has not been established. This was a subanalysis of the SWITCH-SEMA 1 study, a multicenter, prospective, randomized, parallel-group trial comparing switching from liraglutide or dulaglutide to once-weekly semaglutide in subjects with T2DM (SWITCH) versus continuing current GLP-1RAs (Continue) for 24 weeks. This subanalysis consisted of participants who were suspected to have NAFLD [fatty liver index (FLI) ≥ 30]. In total, 58 participants met the criteria of this subanalysis. There were no statistical differences in baseline characteristics between the SWITCH (n = 31) and Continue groups (n = 27). FLI significantly improved during treatment in the SWITCH group (68.6 to 62.7) but not in the Continue group (71.1 to 72.3) (p < 0.01). The improvement of FLI in the SWITCH group was greater in switching from dulaglutide to semaglutide and significantly correlated with older age (p = 0.016) and lower baseline FLI (p < 0.01). The multiple linear regression analysis revealed that the switch from dulaglutide was associated with an improvement in FLI (p = 0.041). Switching from conventional GLP-1RAs to once-weekly semaglutide might be beneficial for individuals with NAFLD complicated with T2DM.